Factors affecting student’s perception towards online learning during Covid 19 pandemic - Choo, Zhe Yan; Siao, Jeffrey Chin Khen; Teh, E-Hang; Roeshan, Suntra Murthi; Wong, Zhi Fong (2021)
The primary goal of this research study is to survey the students’ perception on online learning during the COVID-19 pandemic in Malaysia. We have anticipated a couple of hypothesis to study the relationship between the dependent (students’ perception on online learning) and independent variables (students’ attitudes, students’ self-efficacy, technical conditions, study methods). We have also delivered the related literature reviews and the projected structure for this research. Through this research, we focus on identifying the significant relationship between the factors that affect the students’ perception on online learning and their attitudes. The respondents that we targeted are students from UTAR. We did our part of collecting and analysing the data which resulted in us succeeding in our study. The results show that students’ attitudes, students’ self-efficacy, technical conditions and study methods are significantly correlated with the students’ perception on online learning. To sum up, the university should consider the students’ attitudes and the technical conditions for them to have a good perception on online learning.